2010
DOI: 10.1530/rep-09-0485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of puberty and gonadotropins on the molecular events controlling meiotic resumption of mouse oocytes

Abstract: Although studies suggest that the low competence of oocytes from prepubertal animals is due to their insufficient cytoplasmic maturation and that FSH improves oocyte maturation possibly by retarding meiotic progression and allowing more time for cytoplasmic maturation, the mechanisms by which puberty and gonadotropins regulate meiotic progression require additional detailed studies. For the first time, we observed that while meiotic progression was significantly slower, the maturation-promoting factor (MPF) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
6
1
Order By: Relevance
“…The low cAMP levels prior to and after IVM in adult and prepubertal oocytes cultured without cAMP modulators, indicate that cAMP levels drop immediately after follicle aspiration and then remain at low levels through meiosis under in vitro conditions. Our results provide compelling evidence that prepubertal oocytes produce and/or receive cAMP from cumulus cells in response to cAMP modulators similar to adult oocytes, suggesting that this pathway is already functional in prepubertal bovine oocytes, which is in apparent contrast to previous reports in mice and pig prepubertal models [ 3 , 4 ].…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…The low cAMP levels prior to and after IVM in adult and prepubertal oocytes cultured without cAMP modulators, indicate that cAMP levels drop immediately after follicle aspiration and then remain at low levels through meiosis under in vitro conditions. Our results provide compelling evidence that prepubertal oocytes produce and/or receive cAMP from cumulus cells in response to cAMP modulators similar to adult oocytes, suggesting that this pathway is already functional in prepubertal bovine oocytes, which is in apparent contrast to previous reports in mice and pig prepubertal models [ 3 , 4 ].…”
Section: Discussioncontrasting
confidence: 41%
“…Cyclic AMP controls meiotic progression in fetal ovaries, and is involved in the establishment of the primordial follicle pool [ 2 ]. However, the ability to accumulate cAMP is reduced in oocytes from prepubertal pigs [ 3 ] and mice [ 4 ]. Since the oocyte receives cAMP from the adjacent cumulus cells via gap junctions, the lower cAMP levels associated with lower developmental capacity in prepubertal oocytes have been linked either to decreased LH/FSH ovarian receptor expression [ 5 ], altered adenylate cyclase response [ 4 ], different phosphodiesterase (PDE) activities [ 4 ], and/or defective gap junction communication [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…To rule out the possibility that these cytokinetic disorders were secondary to delayed GVBD, we performed a set of drug treatment experiments on post-GVBD oocytes. To further confirm that the abnormal cytokinetic results were directly caused by cAMP and its downstream factors, we treated post-GVBD oocytes with a adenylate cyclase activator, forskolin [43], [44], [45], and a PKA inhibitor, H-89 [46], [47], to determine their effects on cytokinesis. As shown in Figure 2, all three cAMP-elevating chemicals promoted both the “2-cell” and “1-cell” type division patterns.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that incompetent goat oocytes have a limited amount of cyclin B1 (Hue et al 1997) and p34 cdc2 . MPF activity in calf and lamb oocytes were significantly lower than in cow and ewe oocytes (Ledda et al 2001, Salamone et al 2001, whereas (Han et al 2010) showed in mice that the MPF activity of prepubertal oocytes was significantly higher than that of adult oocytes. In prepubertal goats, Anguita et al (2007) showed higher MPF activity and oocyte competence to develop up to the blastocyst stage in oocytes with a diameter larger than 135 mm.…”
Section: Introductionmentioning
confidence: 84%